Disentangling the effects of multiple fires on spatially interspersed sagebrush (Artemisia spp.) communities. (27th September 2020) - Shinneman, Douglas J.; McIlroy, Susan K.; de Graaff, Marie‐Anne
Abstract: Questions: Relative to a landscape with a mosaic of two sagebrush community types and increasing fire frequency, we asked: (a) do vegetation characteristics vary significantly with number of times burned for each sagebrush community; (b) how do vegetation responses to different fire frequencies compare between the two sagebrush communities? Location: Columbia Plateau Ecoregion, Washington, USA. Methods: We sampled vegetation across a landscape that burned three times over a 10‐year period in two sagebrush community types that are interspersed on unique land forms: big sagebrush ( Artemisia tridentata ) communities that occur on small "mounds" and scabland sagebrush ( A. rigida ) communities that occur on surrounding "flats." Spatially overlapping fires permitted a balanced sampling design to assess unburned and once‐, twice‐, and thrice‐burned locations for each land form/community type. We utilized a suite of statistical analyses to determine differences among plant functional groups and biomass among unburned/burned strata by land form and compared results between land forms. Results: Big sagebrush and scabland sagebrush communities responded uniquely to multiple fires, due to different fuel loadings, fire severities, succession and invasion dynamics. Big sagebrush experienced nearly complete shrub loss and conversion from exotic‐invaded shrubland to exotic annual grassland after only one fire. In contrast, scabland sagebrush retained a minor shrub component and higher relative cover of native herbaceous species, even after three fires. Both communities retained cover of native perennial grasses, including shallow‐ and deep‐rooted species, likely reflecting decreasing fire intensity with number of times burned. Conclusions: Despite different community‐level responses, increasing fire frequency is transforming the entire landscape to a non‐native/native grassland mix. Quantifying unique ecosystem responses to altered wildfire regimes is critical to understanding the relative resilience of communities to disturbance and their resistance to exotic species invasion (and community type conversion). Management actions may help to maintain spatial heterogeneity of ecosystems and fire‐tolerant native species. Abstract : This study investigated vegetation response across a landscape that burned three times over a 10‐year period across two interspersed sagebrush community types. Big sagebrush and scabland sagebrush communities responded uniquely to multiple fires, with distinct succession and exotic species invasion dynamics likely influenced in part by different fuel loadings that influenced fire severity. Despite different community‐level responses, increasing fire frequency is transforming the entire landscape to a non‐native/native grassland mix.